KOMUNIKASI PENGAWAS DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR DI KECAMATAN SOMBA OPU KABUPATEN GOWA - Kamaluddin Tajibu (Jurnal Dakwah Tabligh, 2019)
The supervision process carried out by the Supervisor and Principal aims to improve the performance of the teachers. The teacher's performance includes the ability to prepare teaching materials, choose media learning, carry out learning and evaluate learning activities. For this reason supervisors in carrying out supervision activities must adopt a communication strategy that includes interpersonal communication, group communication and mass communication. However, in the implementation of supervision, supervisors experienced various obstacles including: Clarity of roles and tasks, Policy Structure, Communication Ability of Local and National Leader Support Supervisors.